An Analysis of Semiotic In Queen’s Song “Bohemian Rhapsody” - Syamsu T; Andi Asrifan; Andi Sadapotto; Emy Nur Rahmayani; suleha .; abdul Kahar (La Ogi : English Language Journal, 2023)
Analyzing data is an activity of thinking and recognizing data which is then described so that it becomes component signs. Regarding signs, in studying English several sciences need to be studied, one of which is semiotics. Semiotics is the study of signs contained in objects that have specific meanings. In this study the researcher wanted to analyze song from Band Queen, namely Bohemian Rhapsody, "Bohemian Rhapsody" is a song with various genre transitions, modulations, and tempos, changes to several genres and modulations that occur repeatedly in the song are closely related to how the structure is of the song is contained in it. This song has a hidden meaning and message, so the researcher wants to examine this song by using the theory from Roland Barthes which discusses connotation, denotation, and myth which are in line with the researcher's wishes. The method used in this research is the descriptive qualitative method. In this study, the researcher collected primary data obtained from the lyrics of the Bohemian Rhapsody song. This data includes themes, schemes, word meanings, and word stress in the lyrics of the Bohemian Rhapsody song. After the data were categorized according to Roland Barthes' theory, the data were then analyzed descriptively to answer this research question. After that, the researcher conducted a literature study by looking for references through literature both from books, document journals, and other related sources and other topics relevant to this research. The results of the study show that there are 7 parts of the stanza which are then interpreted using the Roland Barthes method, where almost every stanza discusses the feeling of regret experienced by the songwriter.